Illicit drug use and exposure in disadvantaged neighborhoods in Czechia: policy representations and evidence - Kupka, Petr; Petruželka, Benjamin; Walach, Václav (Journal of ethnicity in substance abuse, 2022)
This study examines the lifetime prevalence of illicit drug use and illicit drug exposure in disadvantaged ("Roma") and more affluent neighborhoods in Czechia. The results of a survey among populations of both types of neighborhoods suggest no statistically significant difference between the two in terms of the overall lifetime prevalence of illicit drug use; however, lifetime prevalence of methamphetamine use proved higher in disadvantaged neighborhoods. The population of disadvantaged neighborhoods has also lower chances to use LSD during their lifetime. Further differences were identified in drug exposure, with the population of more affluent neighborhoods being more frequently exposed to illicit drugs than the population of disadvantaged neighborhoods. The predictors of drug use and drug exposure were partially different for both populations. In the disadvantaged population, drug use was revealed, among other predictors, to be associated with housing conditions.
Keywords: poruchy spojené s užíváním psychoaktivních látek; zakázané drogy; postup; illicit drugs; drug exposure; charakteristiky bydlení; Residence Characteristics; Substance-Related Disorders; Humans; Vulnerable Populations; Česká republika; drug use; Illicit Drugs; lidé; Disadvantaged neighborhoods; zranitelné populace; Policy; Czech Republic